Increasing ploidy level of marigold (Tagetes patula Sudamala Barak) using colchicine with acute and chronic methods - YUYUN NITA SARI; SYARIFAH IIS AISYAH; DEWI SUKMA; MUHAMAD SYUKUR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sari YN, Aisyah SI, Sukma D, Syukur M. 2025. Increasing ploidy level of marigold (Tagetes patula Sudamala Barak) using colchicine with acute and chronic methods. Biodiversitas 26: 2726-2734. Marigold (Tagetes sp.) is a popular and potential ornamental plant in Indonesia, especially in Bali, commonly used in religious ceremonies and industry. A significant challenge in the floriculture industry is producing plants with desirable traits, such as larger flowers. Sudamala Barak has dark red flowers with small size (4,5-5,6 cm), but consumers prefer larger ones (8-10 cm). Colchicine is a chemical mutagen that disrupts spindle fiber formation during mitosis, thereby inducing chromosome doubling and resulting in polyploid cells. Tagetes patula is an allotetraploid species (2n = 48). This study aimed to determine the LC50 value and analyze the morphological, histological, and cytological characteristics of Sudamala Barak mutants. The research was conducted from May 2024 to February 2025 using two application methods: acute (seven concentrations) and chronic (four concentrations) based on LC50 (lethal concentration 50%). The results showed that colchicine significantly affected various plant characteristics. The LC50 value was found to be 0.346%. Overall, the chronic method produced greater diversity than the acute method. Colchicine treatment influenced plant height, canopy width, number of primary branches, stem diameter, flowering time, and flower diameter. It also increased the number of stomata and chloroplasts, potentially improving photosynthetic efficiency. In the acute method, the highest ploidy level was euploid-pentaploid (2n = 60) at concentrations of 0.05%; 0.1%; 0.15%; 0.25%; and 0.3%. In contrast, in the chronic method, the highest ploidy level was euploid-autoalooctaploid (2n = 96) at 10× and 20× LC50 dilution concentrations.